The Phenomenon of Teenagers Shopping Online in Tamalanrea District, Makassar City - Rintoh, Rintoh (Journal of Entrepreneur, Business and Management, 2024)
Adolescence is a period of searching for one's identity to be more accepted in one's environment. Today's teenagers are a generation that understands technology and relies more on technology for their activities. One of their activities that relies on technology is online shopping. This research uses a methodology with a qualitative approach and uses phenomenological theory by interviewing four teenagers who are students. The informant's criteria is that they shop online almost every day. The aim of this research is to find out why teenagers like shopping via e-commerce. The results of the research found that today's teenagers prefer things that are practical and easy. Being equipped with technological capabilities makes it easier for them to shop without worry. They use the features offered within reasonable limits because they understand the consequences of these features. Therefore, they feel they can still survive in the big city (Makassar) without worrying and still follow the latest fashion.Keywords: teenagers, e-commerce, online